ANDROID APPLICATION DEVELOPMENT IN ENERGY DISAGREGATION WITH THE HIDDED MARKOV FACTORIAL METHOD (FHMM) BASED ON INTERNET OF THING (IOT) - Sidik, Rizki
that energy savings are needed, one of which is saving electrical energy. In the process of effective electrical energy saving, users need to know the consumption of the electrical energy structure of each device that can be monitored anytime and anywhere via a smartphone. In this study, an android application was developed as a user interface to monitor household energy consumption with the energy disaggregation method. In the process of sending data, Internet of Things (IoT) technology is used so that data can be sent, processed, and displayed on the user interface. The disaggregation method used is the Factorial Hidden Markov Model (FHMM). This research is a simulation to test the disaggregation method and android application using the ampds data set. The data set will be processed by node-red for the energy disaggregation process using the FHMM method and stored by the influx-db database, then the results of the data processing will be accessed and displayed by the android application. The accuracy of the results of energy disaggregation using the FHMM method in this study was 85%. In this simulation, the developed android application has succeeded in accessing data from the server and can display on and off status, expenditure history, energy consumption structure, expenditure percentage and cost of each device in the form of attractive images and graphics.